Welfare impacts of air quality changes in Malaysia: the hedonic pricing approach - Jamal Othman; Redzuan Othman; Nor Ghani Md. Nor (Penerbit Universiti Kebangsaan Malaysia, 2006)
This study employs the Hedonic Pricing Model (HPM) to assess the weIfare impacts of air quality changes in Malaysia. Results from second stage HPM indicate that households on average derive benefits (welfare gain) of some RM19 for every unit of improvement in air quality index (API) in relation to the baseline API level. This finding provides an insight of the magnitude of welfare gain or loss due to air quality changes.